Pendugaan Kerusakan Mangga Arumanis Akibat Lalat Buah Menggunakan Atenuasi Ultrasonik - Warji .; Rokhani Hasbullah (PERTETA, 2008)
The objectives of this research were to determine attenuation coefficient of arumanis mangoes, to develop border equation prediction and to validate the border equation prediction of arumanis mangoes damage caused by fruit fly using ultrasonic attenuation coefficient. The method was-based on measurement of attenuation coefficient ultrasonic wave in arumanis mangoes. Results showed that mean of normal arumanis mangoes attenuation coefficient was 36.45 Nplm and attenuation of arumanis mangoes damage caused by fruit fly was 30.67 NPlm. Border equation prediction was attenuation coefficient more than 34.76 for normal mango and attenuation less than or same 34.76 for mangoes invested by fruit fly. Keywords: arumanis mangoes, fruit fly, ultrasonic, attenuation coefficient.